Politeness Maxims In Character Interaction In The Last Of Us 2 Video Game - Erlita Vierra Trirenata; Mahi M Hkikmat; Ice Sariyati (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aimed to identify politeness maxims used in the characters' dialogue in The Last of Us 2 video game. The study used Geoffrey Leech's theory of politeness maxim. This research focused on what types of politeness maxim appeared in the dialogue and how characters used those types of politeness. This study used descriptive-qualitative for its research method. The object of this research was the dialogue between characters in The Last of Us 2 video game. The result of this research showed that there were 40 data that contained maxims of politeness. There were 14 data for maxim tact, 6 data for maxim generosity, 6 data for maxim approbation, 2 data for maxim modesty, 3 data for maxim agreement, and 9 data for maxim sympathy. Maxim tact was the most frequently used by the characters in The Last of Us 2 video game. The use of these maxims plays a significant role in shaping the narrative and portraying the relationship between characters, which created efficient communication.